ASBABUN NUZUL AL-QUR’AN DALAM PERSPEKTIF MIKRO DAN MAKRO - Nunung Susfita (Universitas Islam Negeri (UIN) Mataram, 2015)
Al-Qur’an has been sent down to give guidance to people toward the bright goal and straight way by maintaining origin of life which is based on faith in Allah and his treatise. Al-Qur’an also tells the past story, events happen now and information will happen in future. Most of contains of al-Qur’an firstly were sent down to general purposes but life of disciple of the messenger saw many historical events and sometimes special events happened to them and needed the explanation from law of Allah or thatlaw was still unclear for them, and then they asked to the messenger to know the Islamic law about that thing. So, al-Qur’an sent down to the special events or to the questions appeared. It almost become axiomatic argumentation that thereis no text, anything the form, which come to empty room. It is always related to the event therefore the text is always complex. Activity of alQur’an interpretation is an activity to see and examine validity of a text for human life, especially for Islamic people. As we know that text is not always relevant, it always must beused or thought with reality or with interest; no matter what form and here alQur’an text will become “live”.